2016
DOI: 10.1002/poc.3572
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of xanthene‐based covalently linked dimers

Abstract: The conformational flexibility of three covalently linked dimers consisting of two xanthene‐based moieties connected by a diphenyl ether linker was studied using NMR spectroscopy, X‐ray crystallography, and density functional theory (DFT) calculations. The three dimers interconvert as a function of pH: the doubly cationic dimer (Xan+)2 exists in acidic solutions (pH < 0.5), the mono‐alcohol monocation Xan+–Xan‐OH at intermediate pH values (pH = 1–3), and the neutral diol at the highest pH‐values (pH > 3). Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…The instability of the C form of BP(OH) 2 was not investigated further. It might involve an intramolecular Friedel‐Crafts reactivity as was observed previously for the DPE(OH) 2 dication …”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…The instability of the C form of BP(OH) 2 was not investigated further. It might involve an intramolecular Friedel‐Crafts reactivity as was observed previously for the DPE(OH) 2 dication …”
Section: Resultssupporting
confidence: 53%
“…As pH is decreased, the PB form of XAN(OH) 2 is formed and can be identified by its absorption bands at 363 and 460 nm. The PB pK a values were determined from photometric titration data and were found to correlate with the electronic factors that affect the stability of the cationic forms: pK a = 1.3 for MONO(OH), pK a1 = 0.2 and pK a2 = 2.6 for DPE(OH) 2 , pK a1 = 1.3 and pK a2 = 3.5 for XAN(OH) 2 (Figure B). It was found that the cationic forms of MONO(OH) and DPE(OH) 2 react readily with water to form PB derivatives, while the equivalent conversion of XAN(OH) 2 required several hours and elevated temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations